Efforts to increase the selling value of pure cow's milk into fresh processed milk products in Bekiring Village - P, A Vickania; Kusnawan, Wawan; Kurniawati, Varisa; P, Nasfa Brilianingtyas; F, Shinta Vega; B, Sely Aprilana Angelima (CV. BImbingan Belajar Assyfa, 2023)
Bekiring Village is an area with a large population. There are many livelihoods as cattle farms so that pure cow's milk yield is relatively abundant. Many residents who work as cattle breeders have their own background, namely that previously, the residents were workers and managed cloves in Bekiring Village. However, the residents changed their jobs to become cattle breeders because of an epidemic that could not be handled. Cows that are cared for are the main source of livelihood for local residents, from delivering pure milk to shops or factories that will process the milk into a product that can be consumed properly. It is known that the advantage of whole milk is that it is a food ingredient that has high nutritional value. However, cow's milk is easily damaged if handled poorly, as it spoils easily and can cause illness if consumed. Therefore, innovation is needed in processing pure cow's milk into processed products with a more economical and nutritious selling value, such as fresh bekiring milk drinks. 1) Providing knowledge to the community regarding the economic potential of pure cow's milk, 2) providing insight to PKK mothers regarding how to process pure cow's milk into ready-to-drink milk products, and 3) skills training for the community regarding processing pure cow's milk.